Analysis of Factors Related to the Incidence of Stunting in Fishermen's Children Aged 12-24 Months - Delsy Nurrizma; Delmi Sulatri; Syamel Muhammad (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2023)
Stunting is a condition of growth failure in a child's body length of less than -2 standard deviations based on World Health Organization, standards due to manifestations of long-term malnutrition, recurrent infectious diseases, and inadequate psychosocial stimulation. The research aims to determine the analysis of factors related to the incidence of stunting in children aged 12-24 months in the Air Bangis Health Center working area in 2020. The research is a Mix Method Study with a Sequential Explanatory design carried out in the Air Bangis Health Center Working Area in 2022. This research was conducted in the Air Bangis Health Center Work Area from November to February 2023. The research quantitatively conducted a Cross-Sectional Study on children aged 12-24 months, as many as 148 people and their mothers. Measurement of body length according to age, questionnaires for quantitative data, and in-depth interviews for qualitative data. The logistic regression test determines the most dominant variable that causes stunting. There is a significant relationship between food intake (p-value=0.042), sanitation (p-value=0.013), immunization status (p-value=0.117), and maternal education (p-value=0.095) on the incidence of stunting. There is no relationship between exclusive breastfeeding, infectious diseases, hygiene and family income. The most dominant factor is food intake, with value (POR=2.220). Based on the research results, it was found that the most dominant variable was food intake. It is recommended for mothers of toddlers to pay more attention to nutritional intake during pregnancy and breastfeeding and it is recommended for health workers to provide education in the form of health education about nutritious foods to prospective pregnant mothers to pay more attention to their nutritional intake. Keywords: Intake, Nutrition, Sanitation, Stunting